OHP-047 Impact of the Economic Crisis on Biomedical Research: Analysis of the Work of a Clinical Research Ethics Committee. (12th March 2013) - Arcenillas, P; Redondo, S; Giménez, N; March, P; Soriano, L; Pla, R; Quintana, S
Abstract : Background: Since 2008, the economic crisis has directly affected many activities, health and biomedical research being particular fields involved. Purpose: To evaluate the impact of the economic crisis on research at a Spanish hospital based on an analysis on the work done by the Clinical Research Ethics Committee (CEIC). To compare it with any effects on Spanish and European CTs. Materials and Methods: CEIC Minutes from a 500-bed university hospital were reviewed from 2000 to 2011, obtaining information from clinical trials (CTs) and observational studies (OS). The financing of CTs was classified: 1) CTs promoted by the pharmaceutical industry, 2) by scientific societies with industry support, 3) by scientific societies with government support and 4) unfunded CTs. We compared two periods: pre-crisis (2000–2007) and crisis (2008–2011). National scientific activity was obtained from a secondary data source from the information provided by the Agencia Española de Medicamentos y Productos Sanitarios and the European activity from EU Clinical Trials Registers (European Medicines Agency website). Data analysis used conventional descriptive statistics. Results: 782 protocols were evaluated (average 71 protocols/year). During 2008–2011 there was an annual average decrease of 13 CT in groups 1 and 2, compared with the period 2000–2007 (95% CI: 4–22 CT). Regarding the OSs, there was an annual average increase of 36 OSs during the second period (95% CI: 24–49 OS). There were no statistical differences between the two periods for groups 3 and 4. The total number of protocols increased by an average of 25 projects/year during the second period compared to the first (95% CI: 8–40 projects). There were 2340 CTs in Spain during the first period and 3096 during the second (p = ns). CTs in Europe were 7, 908 and 10, 632 respectively (p = ns). Conclusions: The CEIC workload was maintained, even increased, but because of OSs and unfunded research. The crisis marked a turning point; funded studies decreased and OSs increased. At the moment there are no noteworthy changes in Spanish or European CT activity. No conflict of interest.